Impact of Social Networking and Technology on Knowledge Sharing among Undergraduate Students - Ahmad, Abd Rahman; Jameel, Alaa S; Raewf, Manaf B (International Business Education Journal, 2021)
Effective and inclusive Knowledge Sharing is an integral part of successful and practical university learning. This study examines the factors impacting Knowledge sharing among students as there is a lack of studies conducted among students in the context of middle east countries. A survey was carried out among undergraduate students at Cihan University-Erbil, Iraq and questionnaires consisted of two main sections were used to collect the data. Demographic information was collected in the first section, and the second section contained six factors: File-sharing, Perceived Enjoyment, Perceived Reciprocal Benefit, Information and Communication Technology, Technology Availability, and Knowledge Sharing. Out of 150 questionnaires distributed, 114 were valid for analysis representing a 76% response rate and the data were analysed using Smart-PLS 3.2.9. The results indicated that Files-sharing, Perceived Enjoyment, Perceived Reciprocal Benefit, and Information and Communication Technology positively impacted Knowledge Sharing among students. However, Technology Availability did not affect Knowledge Sharing among students. The results implied that universities should encourage Knowledge Sharing between students by designing course activities and assessment that incorporate Files-sharing and Information and Communication Technology by fostering enjoyment and creating awareness of Knowledge Sharing’s reciprocal benefits.